012 Mechanical thrombectomy in pediatric stroke: systematic review, individual patient-data meta-analysis, and case series. (29th July 2019) - Bhatia, Kartik; Kortman, Hans; Blair, Chris; Parker, Geoffrey; Brunacci, David; Ang, Tim; Worthington, John; Muthusami, Prakash; Krings, Timo
Abstract : Introduction: In adults, there is strong evidence demonstrating the superiority of mechanical thrombectomy (MT) plus intravenous thrombolysis over thrombolysis alone for the treatment of acute ischemic stroke due to large vessel occlusion (LVO). The role of MT in the paediatric stroke population is less clear. Here we present an updated systematic review addressing the use of MT in paediatric patients, including three cases from our centre in Sydney, Australia. We have also completed an individual participant data (IPD) meta-analysis of clinical and angiographic outcomes based on these results. Method: Our systematic review and IPD meta-analysis was performed according to PRISMA-IPD (Preferred Reporting Items for Systematic Reviews and Meta-Analyses: Individual Participant Data) guidelines. Primary outcomes measures were change in NIHSS (National Institute of Health Stroke Scale) score following MT, and mRS (modified Rankin Scale) score at final reported follow-up. The secondary outcome measure was final angiographic result using the mTICI (modified Treatment in Cerebral Ischemia) scale. Results: MT resulted in good long-term neurological outcomes (mRS 0–2) in 60/67 cases (89.6%;follow-up timing µ=4.1 months: 95%CI 2.9–5.3), good short-term neurological outcomes (reduction in NIHSS by 8 or more points or post-MT NIHSS of 0–1) in 37/52 cases (71.2%), and successful recanalization (mTICI 2b/3) in 57/67 cases (85.1%). Conclusions In paediatric patients, MT is an effective treatment for ischaemic stroke due to LVO. In the absence of a dedicated prospective registry and with randomized control trails unfeasible, this report represents the best available evidence for the use of MT in the paediatric setting.